Doing the Camino de Santiago (II) (Journal of Parents and Teachers, 2013)
This is the second article of a serie of three of them that wants to show the essential part of the Camino de Santiago. It offers a description, insisting on the architectonic and cultural value of the part of the Camino de Santiago from Burgos to the Cruz del Ferro and the Camino Gallego. The article is completed with a didactic guide.
Keywords: Camino de Santiago; art; Spain; cultural heritage; didactic material; education.